2021
DOI: 10.3389/fpsyg.2021.625654
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Fear of Cancer Recurrence in Family Caregivers of Cancer Survivors: A Systematic Review

Abstract: Objective: Fear of cancer recurrence (FCR) is a significant concern for family caregivers of cancer survivors and is associated with many adverse outcomes, including increased emotional distress and poorer quality of life. Although several theoretical models have been proposed to account for FCR in cancer survivors, their applicability to caregivers is unknown. The aim of this review was to identify clinical, demographic and psychological factors that are associated with, and predict, FCR in caregivers of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 69 publications
4
21
1
Order By: Relevance
“…Contrary to prior literature, 9,32 we found that many participants were in a constant state of planning and preparation for the "worstcase scenario" (i.e., the death of the patient). It is possible that this hypervigilant behavioural preparation was an attempt to compensate for a caregiver's sense of being cognitively and emotionally unprepared for the loss of the patient.…”
Section: Unprepared For the Worstcontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to prior literature, 9,32 we found that many participants were in a constant state of planning and preparation for the "worstcase scenario" (i.e., the death of the patient). It is possible that this hypervigilant behavioural preparation was an attempt to compensate for a caregiver's sense of being cognitively and emotionally unprepared for the loss of the patient.…”
Section: Unprepared For the Worstcontrasting
confidence: 99%
“…Meta‐analytic evidence suggests that 46% of caregivers experience FCR at levels that would be considered clinically significant in patient populations 8 . Three recent systematic reviews further suggest that caregivers experience FCR at levels equal to or higher than those they care for 8–10 . Smith and colleagues 10 proposed that, like distress, 11 there is a bidirectional relationship between patient and caregiver FCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of progression (FoP), or fear of recurrence or relapse, is defined as the “fear that the illness will progress with all its biopsychosocial consequences, or that it will recur” 3 . FoP has been extensively studied in the past decades in both, adult cancer patients and their caregivers 4,5 ; however, little is known regarding the FoP among parents of children undergoing cancer treatment 6 …”
Section: Introductionmentioning
confidence: 99%
“…2 Fear of progression (FoP), or fear of recurrence or relapse, is defined as the "fear that the illness will progress with all its biopsychosocial consequences, or that it will recur". 3 FoP has been extensively studied in the past decades in both, adult cancer patients and their caregivers 4,5 ; however, little is known regarding the FoP among parents of children undergoing cancer treatment. 6 Dysfunctional levels of FoP have been observed in 48.3%-61.9% of parents of childhood cancer patients 6,7 ; this proportion is considerably higher than that in adult cancer patients and their partners.…”
mentioning
confidence: 99%